Acquired Bernard–Soulier syndrome and hypodysfibrinogenaemia because of multiple myeloma. Issue 2 (March 2022) - Sehgal, Tushar; Altohami, Mohammed; Lafferty, Nicholas; Desborough, Michael; Boyce, Sara; Kazmi, Rashid; Jenner, Matthew
Abstract : N/A: We describe a case of a patient with multiple myeloma with initial presentation simulating a bleeding disorder. Detailed coagulation work-up showed hypodysfibrinogenaemia along with a platelet function defect consistent with acquired Bernard–Soulier syndrome (BSS). Multiple plasma exchanges led to significant improvement in his bleeding symptoms. To the best of our knowledge, this is the first described case of simultaneous presentation of hypodysfibrinogenaemia and BSS secondary to multiple myeloma.